The Double Standard Toward Female and Male Victims of Non-consensual Dissemination of Intimate Images - Zvi, Liza (Journal of interpersonal violence, 2022)
Non-consensual dissemination of intimate images (NCII) is a growing problem of sexual violence with grave consequences for victims. However, despite recent criminalization and civil and legal sanctions, there is reason to suspect that the majority of NCII cases remain unreported. The reasons for that may be similar to the ones accounting for under-reporting in cases of physical sexual violence and are tied to society?s attitude toward victims. Being a relatively new form of violence, psychological research on perceptions of NCII victims and offenders is scarce. The purpose of the present study was to extend the current knowledge by comparing perceptions toward female and male victims of NCII, while manipulating the victim?s role in producing the intimate material. Drawing on rape research, it was hypothesized that gender stereotypes interact with victims? sex and behavior to influence the way victims are perceived. Five-hundred and thirty-nine male and female students were presented with a scenario depicting an NCII offense in which the intimate material was either self-generated by the victim (selfies) or stealth-taken by the victim?s ex-intimate partner. Victim and offender sex were also manipulated. The findings indicate a differential treatment toward female and male victims of NCII, depending on their role in the taking of the intimate images. More blaming was attributed toward a female victim whose intimate images were self-taken, in comparison to all other research conditions, and negative feelings toward her were the highest as well. These blame attributions, as well as negative feelings toward female victims, were particularly high on the side of male participants. The findings are interpreted as reflecting perceptions of traditional gender roles and a double standard toward female and male sexual behavior.